The Orion Center bibliography of the Dead Sea scrolls and associated literature (2000-2006) - Clements, Ruth (Studies on the texts of the desert of Judah, 2007)
Presents the bibliography of scholarship on the Dead Sea Scrolls, Qumran, and related fields (including New Testament studies); source, subject, and language indices facilitate its use by scholars and students within and outside the field.